2017
DOI: 10.1016/j.autrev.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic and cost burden of systemic sclerosis: A review of the literature

Abstract: Overall, there is a paucity of information on the burden of SSc. Nonetheless, our review indicates that the quality of life of patients with SSc is considerably lower than that of the general population. In addition, SSc places a considerable economic burden on health care systems and society as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…Given the considerable comorbidity burden of SSc and the availability of limited, and only partly effective, treatment options, it is not surprising that substantial healthcare costs associated with SSc have been reported 12 . However, the economic burden of SSc has been estimated in a limited number of studies [12][13][14][15][16][17] , with only 2 such studies 18,19 including US patients. One of them (Furst,et al 18 ) found that patients with SSc had significantly higher annual healthcare costs and healthcare resource utilization (HRU) than matched controls but only included data up to 2008, and thus may be outdated and not reflective of the current treatment landscape.…”
mentioning
confidence: 99%
“…Given the considerable comorbidity burden of SSc and the availability of limited, and only partly effective, treatment options, it is not surprising that substantial healthcare costs associated with SSc have been reported 12 . However, the economic burden of SSc has been estimated in a limited number of studies [12][13][14][15][16][17] , with only 2 such studies 18,19 including US patients. One of them (Furst,et al 18 ) found that patients with SSc had significantly higher annual healthcare costs and healthcare resource utilization (HRU) than matched controls but only included data up to 2008, and thus may be outdated and not reflective of the current treatment landscape.…”
mentioning
confidence: 99%
“…Estimated cumulative 10‐year survival is between 56–78%, depending on the disease severity (Rubio‐Rivas, Royo, Simeon, Corbella, & Fonollosa, ). Although the total number of affected SSc patients per country is low, the economic and human burden is high (Fischer, Zimovetz, Ling, Esser, & Schoof, ). SSc patients are high users of healthcare resources and have high annual medical costs—particularly those patients with serious disease complications and more functional disability (Chevreul, Brigham, Gandre, Mouthon, & Network, ; Meijs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The systemic connective tissue diseases (SCTD) including systemic vasculitis, systemic lupus erythematosus (SLE), systemic sclerosis (SSc), Sjögren syndrome, polymyositis and dermatomyositis are a group of chronic inflammatory systemic autoimmune disorders associated with disability, pain, deterioration in quality of life, morbidity and excess mortality . These disorders are also associated with substantial health care costs and productivity losses (work disability, early retirement) imposing significant economic burden on patients, healthcare systems and societies . For instance, there was a 3‐fold difference in total costs for SLE in an incipient cohort compared with matched population controls in southern Sweden .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there was a 3‐fold difference in total costs for SLE in an incipient cohort compared with matched population controls in southern Sweden . Hospitalizations are a key driver of healthcare costs among people with SCTD . A recent study estimated that 58% of total healthcare costs of Swedish patients with SLE were attributed to hospitalization .…”
Section: Introductionmentioning
confidence: 99%